(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
The compact antenna for on-body applications is designed for covering ISM frequency bands. The antenna covering ISM frequency bands in range of 2.45 and 5.8 GHz. The circular structure with triangular slots is responsible for obtaining the dual band applications. The antenna designed on flexible polyimide substrate having dielectric constant of 3.5 with loss tangent of 0.008. The bending analysis of the antenna is performed to analyze the flexible nature. The proposed antenna covering the frequency range 2.3-3.5 GHz and 5.1-6.8 GHz with fractional bandwidth of 41% and 28%. The antenna provides the stable dipole and omni directional patterns. The measured antenna provides the peak gain of 2.3 dBi at 2.5GHz and 4.7 dBi at 5.8 GHz radiation efficiency of 78% at 2.5 GHz and 84% at 5.8 GHz. To validate the antenna performance antenna undergone for the comparison of simulated and measured results by placing antenna on human body.